(untitled) (College of Basic Education Research Journal, 2011)
A set is said to be dominating set of G if for every thereexistsavertex such that .Theminimum cardinality of vertices among dominating set of G is called the dominationnumberofGdenotedby . WeinvestigatethedominationnumberofTadpolegraph,Bookgraphand StackedBookgraph.Alsowetestour theoretical results incomputerby introducing amatlab procedure to find the domination number , dominating set S and draw this graph that illustrates the vertices of dominationthisgraphs.Itisprovedthat